2019
DOI: 10.1007/s12325-019-01205-z
|View full text |Cite
|
Sign up to set email alerts
|

New Technologies and Applications in Sacral Neuromodulation: An Update

Abstract: Recently rechargeable devices have been introduced for sacral neuromodulation (SNM) with conditional safety for full-body magnetic resonance imaging (MRI). Currently a recharge-free SNM device represents the standard implant; however, it is only approved for MRI head scans. As further new technologies with broader MRI capabilities are emerging, the advantages as well as disadvantages of both rechargeable versus recharge-free devices will be briefly discussed in this commentary from the perspective of patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 24 publications
1
33
0
4
Order By: Relevance
“…Since new full-body MRI-safe devices have become recently commercially available for 1.5 T and 3 T (Axonics, Irvine, CA and Medtronic, Minneapolis, MN), more patients with MS could gain access to this minimally invasive, reversible treatment. New SNM technologies with smaller rechargeable devices (Axonics r-SNM, 5.5 cm 3 ; Medtronic InterStim Micro, 2.8 cm 3 ) with an expected battery life of up to 15 years [ 14 ] offer significant advantages for patients with a need for high stimulation amplitudes, which is not rare among the neurological patient population. In their case series, Minardi et al observed a mean amplitude of 3.6 V (range 2.3–5.8 V) for patients with MS [ 44 ] resulting in a mean battery life of approximately 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since new full-body MRI-safe devices have become recently commercially available for 1.5 T and 3 T (Axonics, Irvine, CA and Medtronic, Minneapolis, MN), more patients with MS could gain access to this minimally invasive, reversible treatment. New SNM technologies with smaller rechargeable devices (Axonics r-SNM, 5.5 cm 3 ; Medtronic InterStim Micro, 2.8 cm 3 ) with an expected battery life of up to 15 years [ 14 ] offer significant advantages for patients with a need for high stimulation amplitudes, which is not rare among the neurological patient population. In their case series, Minardi et al observed a mean amplitude of 3.6 V (range 2.3–5.8 V) for patients with MS [ 44 ] resulting in a mean battery life of approximately 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the current guidelines of the European Association of Urology (EAU) SNM has been described as a treatment for nLUTD, but without concrete guidance or recommendations [ 13 ]. The recently introduced new full-body magnetic resonance imaging (MRI)-safe SNM devices [ 14 ] will offer broader access to a patient group that has often been considered as a contraindication due to the need for regular MRI investigations. For example, in a population-based study of patients with MS, prevalence rates of lower urinary tract symptoms or fecal incontinence were high, at 75% and 29%, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of using a rechargeable system include a reduced number of revision/replacement surgeries (due to the small INS size and device life of 15 years) as well as potentially increased patient comfort and projected lower healthcare costs 19 . This study shows that high patient satisfaction and significant, durable symptom reduction can be achieved with the rechargeable Axonics System without the significant tradeoffs historically reported for rechargeable systems 13,20 . Reasons for high satisfaction with recharging may include unique aspects of the Axonics rechargeable System, such as the small device size, the low recharging burden (short duration of recharging), and optimal implanting INS technique.…”
Section: Discussionmentioning
confidence: 83%
“…The future of neuromodulation is tempting. Miniaturized, rechargeable devices that are safe during full-body MRI scans are being introduced to the market [ 37 ]. It is possible that, in the future, wireless devices generating kHz frequencies capable of blocking pudendal nerve conduction will also be used in the treatment of detrusor sphincter dyssynergia (DSD) in people with spinal cord injuries [ 38 ].…”
Section: Discussionmentioning
confidence: 99%